Outcome in TBI Patients with Early Physiotherapy and Post-discharge Rehabilitation: Indian Experience - Manda, Vijayasekhar Venkata; Pathi, Rajesh; Swaroop, K. Hema; Phaneeswar, T.; Satyavaraprasad, Kadali (Indian Journal of Neurotrauma, 2023)
Introduction Traumatic brain injury (TBI) is a major cause of death and disability worldwide and early initiation of physiotherapy with continuing rehabilitation may improve outcomes.Methods All adult TBI patients with GCS 5–12 admitted from May 2018 to December 2019 were included. Early physiotherapy was initiated before the fifth day of admission and continued post discharge. Patients and families were educated in a rehabilitation program with printed handouts and video clips. All patients are followed up via telephone/video calls after discharge. We assessed the Glasgow Outcome Score (GOS) and disability at 15, 30, and 90 days post discharge, and 180 days follow-up was also suggested but only a few (38) patients reported. Data were compared with matched patients treated in previous years.Results A total of 1,233 patients were studied. At 3-month follow-up by telephonic and video calls, GOS 5 was noted (63.7%; 174/ 273) in 2019 compared with (41.3%; 41/ 98) in 2018. The number of discharges increased after initiation of physiotherapy and rehabilitation programs (38%; 288/759 in 2019 versus 24%; 115/474 in 2018). Post-discharge deaths were also less (5.9%; 17/288) in 2019 compared with (14.8%; 17/115) in 2018.Conclusion Early rehabilitation and post-discharge therapy are associated with improved outcomes of TBI patients. Refinements in data collection and communication improve patient follow-up and functional outcomes.
Keywords: early physiotherapy; communication; GOS; post-discharge rehabilitation; traumatic brain injury